Disentangling vines: a study of morphological crypsis and genetic divergence in vine snakes (Squamata: Colubridae: Ahaetulla) with the description of five new species from Peninsular India - Mallik, Ashok Kumar; Srikanthan, Achyuthan N.; Pal, Saunak P.; D’souza, Princia Margaret; Shanker, Kartik; Ganesh, Sumaithangi Rajagopalan (Zootaxa, 2020)
We carried out a taxonomic revision of Ahaetulla species inhabiting Peninsular India, using a multiple criteria approach (including genetics, morphology, and geography). Our work included populations of the A. nasuta complex (widespread across the entire region, including the Western Ghats), the A. pulverulenta complex (in the Western Ghats, within Peninsular India) and the A. dispar complex (endemic to the Southern Western Ghats) which all revealed undocumented cryptic diversity. Here, we describe five new species and effect nomenclatural changes to some recognised taxa. In the A. nasuta complex, we describe four species from several latitudinal blocks of the Western Ghats and make nomenclatural emendations to the plains populations in the Indian peninsula. We effect nomenclatural change in the A. pulverulenta population of the Western Ghats and describe a new species from the A. dispar group. Our study highlights the use of a multi-criteria approach in unraveling cryptic diversity. This study also reveals a striking case of discordance between morphological and genetic divergence, and the way this is reflected in previous taxonomic and nomenclatural treatments of these populations.